2020
DOI: 10.1186/s12933-020-01128-y
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease and undiagnosed atrial fibrillation in individuals with diabetes

Abstract: Background Diabetes is an independent risk factor for atrial fibrillation (AF), which is associated with increases in mortality and morbidity, as well as a diminished quality of life. Renal involvement in diabetes is common, and since chronic kidney disease (CKD) shares several of the same putative mechanisms as AF, it may contribute to its increased risk in individuals with diabetes. The objective of this study is to identify the relationship between CKD and the rates of newly-diagnosed AF in individuals with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…However, for patients with previously diagnosed CKD, the usefulness of the HF diagnostic algorithm currently proposed may be considered questionable [1] (Figure 2). [1,[10][11][12][13][14][15][16][17]. The HF diagnostic algorithm (left) includes symptoms that are common in patients with CKD, with or without HF (center).…”
Section: How To Confirm or Rule Out Hf In A Patientmentioning
confidence: 99%
“…However, for patients with previously diagnosed CKD, the usefulness of the HF diagnostic algorithm currently proposed may be considered questionable [1] (Figure 2). [1,[10][11][12][13][14][15][16][17]. The HF diagnostic algorithm (left) includes symptoms that are common in patients with CKD, with or without HF (center).…”
Section: How To Confirm or Rule Out Hf In A Patientmentioning
confidence: 99%
“… Not reported Observational Heo et al 30 Older adults, average age 70.9, 68% male mHealth app (screening to prevent strokes) No control group. App positively identified patients at risk for atrial fibrillation App positively identified patients at risk for atrial fibrillation Observational Howland et al 31 Older adults Remote monitoring Patients in the intervention group received more education and communication with providers than the control. Exercise and overall self-care increased.…”
Section: Resultsmentioning
confidence: 99%
“…Der Nutzen dieser vereinfachten EKG-Ableitung im klinischen Einsatz konnte kürzlich gezeigt werden[59]. Andere Systeme nutzen beispielsweise adhäsive Patches, Brustbänder, Armbänder oder auch Hemden mit integrierten Elektroden[9,17,19,28,43].Weiter verbreitet sind die Hand-oder Daumen-EKGs. Diese Geräte…”
unclassified